2023
DOI: 10.1021/acs.langmuir.3c00637
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of ZrO2–SiO2 Antireflective Films with Good Mechanical Performances for Perovskite Solar Cells

Abstract: Antireflective (AR) films are widely applied in solar cells to reduce the reflectivity toward sunlight, thus improving the photoelectric conversion efficiency (PCE) of solar cells. However, AR films are still suffering from poor mechanical properties and low transmittance in photovoltaic applications. Herein, a ZrO2–SiO2 composite film with enhanced mechanical properties was successfully synthesized by a facile sol–gel method, whose pencil hardness increased from less than 6B to B compared with the pure SiO2 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Among the high re ective materials, zirconia had been studied by many scientists due to its excellent performance [20][21][22][23][24][25][26][27][28][29][30][31]. Zirconia had high refractive index, low absorption and low dispersion in visible and near-infrared regions, good chemical stability and good thermal stability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the high re ective materials, zirconia had been studied by many scientists due to its excellent performance [20][21][22][23][24][25][26][27][28][29][30][31]. Zirconia had high refractive index, low absorption and low dispersion in visible and near-infrared regions, good chemical stability and good thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Zirconia had high refractive index, low absorption and low dispersion in visible and near-infrared regions, good chemical stability and good thermal stability. There were researches to improve the LIDT of zirconia coatings [24,[26][27][28]. Zhu et al [26] reported that ZrO 2 coating with ZrOCl 2 •8H 2 O as the precursor and copolymer of silicone and polyaldoxyl ether as the additive had high resistance to laser-induced damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation